Quality and practical aspects of pathological and molecular diagnostics in metastatic colorectal cancer (mCRC) - Tysarowski, Andrzej; Nasierowska-Guttmejer, Anna (Contemporary Oncology/Współczesna Onkologia, 2018)
Colorectal cancer (CRC) is one of the most common malignancies worldwide. In recent years novel therapies targeted at EGFR receptor have been developed. However, this treatment can only be beneficial if no mutation in specific loci of KRAS/NRAS and BRAF genes is found in tumour specimen. Therefore, clinically useful pathological diagnosis of CRC in the era of personalised medicine is a multistep procedure, requiring good cooperation between the clinician/surgeon, pathomorphologist, and molecular biologist. Herein we propose the guidelines of colorectal cancer operating material proceedings for clinicians and pathomorphologists, which determines the correct pathomorphological diagnosis, and we discuss the colorectal cancer molecular biology issues useful in the selection of individual molecular targeted therapy. We discuss and stress the importance of each diagnostic phase: from tumour resection and sample collection at preanalytical stage, through proper pathological preparation, evaluation and selection of material for molecular testing, to molecular analysis and finally preparation of a pathological molecular report.